2015
DOI: 10.1016/j.pedneo.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Different Exogenous Surfactant Preparations on Serial Peripheral Perfusion Index and Tissue Carbon Monoxide Measurements in Preterm Infants with Severe Respiratory Distress Syndrome

Abstract: Patients with RDS had poor perfusion, and PI improved with both surfactant preparations only following a short decline in the 1(st) minute. The expected improvement of PI occurred earlier in the beractant subgroup. TCO declined in both groups, showing lung improvement and decreased oxidative/inflammatory stress, and it was normalized earlier with poractant alfa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Terek et al., comparing effectiveness of Curosurf and Survanta in preterm infants with RDS, mentioned that improvement of perfusion index (PI) was achieved earlier in Survanta group in comparison with Curosurf group. They also reported that inflammatory or oxidative stress was normalized earlier with Curosurf [18] . Eras et al.…”
Section: Discussionmentioning
confidence: 93%
“…Terek et al., comparing effectiveness of Curosurf and Survanta in preterm infants with RDS, mentioned that improvement of perfusion index (PI) was achieved earlier in Survanta group in comparison with Curosurf group. They also reported that inflammatory or oxidative stress was normalized earlier with Curosurf [18] . Eras et al.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, we also searched PubMed, using key words and/or MeSH terms as described in the Additional file 1, looking for animal or human translational investigations on these mechanisms. Fig.1 illustrates the project flow-chart: we included 17 studies in the systematic review [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] and we excluded two papers from the meta-analysis, as they investigated two non-internationally marketed porcine surfactants [43,44]. Compared to our previous metaanalysis on respiratory endpoints, there was one more study reporting on the extra-pulmonary outcomes [45].…”
Section: Additional Analysesmentioning
confidence: 99%
“…These results are only partially similar to those of the earlier Cochrane meta-analysis [8] but they are also stronger. In fact, compared to the previous work we: 1) included five more trials (accounting for ≈600 neonates); 2) used a trials aggregation based on the current best knowledge, that is, on the clinical equivalence of bovine surfactant [8]; 3) analyzed the effect of possible confounders, such as [46][47][48][49] ↓ Prostaglandins synthesis [50,51] ↓ PVR [46,47,[52][53][54] IVH ↓ PaCO2 and CBF [55][56][57] ↓ PDA [53,54] Better peripheral perfusion [34,42] Improved cerebral oxygenation [58] ROP ↓ oxygen and ROS exposure [49,[59][60][61][62][63] NEC ↓ oxygen and ROS exposure [49,64] Better peripheral perfusion [34,42] Earlier progression to full enteral feeding [65][66][67][68] More details in the text. Abbreviations: ROS Reactive oxygen species, PVR Pulmonary vascular resistances, CBF Cerebral blood flow, PaCO2 Arterial partial pressure of CO2, PDA Patent ductus arteriosus, IVH Intraventricular hemorrhage, ROP Retinopathy of prematurity, NEC Necrotizing enterocolitis antenatal steroids or gestational age, and finally, 4) reviewed the possible physiopathological mechanisms linking surfactant replacement and extra-pulmonary outcomes.…”
Section: Summary Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…However, the reduction in oxygen radicals has also been suggested to mediate an indirect beneficial effect on NEC incidence when surfactant is intratracheally given to treat RDS. 38 The classical intratracheal use of surfactant would also entail better peripheral oxygenation and perfusion 39,40 and a quicker progression to full enteral feeding in preterm babies. 41 However, it is not confirmed if these mechanisms can actually influence NEC pathobiology, and it is difficult to think that a single drug administration performed several weeks prior to NEC occurrence in another organ could interfere with its complex physiopathology.…”
Section: Possible Extrapulmonary Surfactant Indicationsmentioning
confidence: 99%